Changes in the crystal lattice of nickel-titanium endodontic instruments as a result of autoclaving - Z. S. Khabadze; M. E. Balashova; A. V. Zoryan; El-Khalaf Ramiz Mohamed; S. M. Abdulkerimova; Yu. A. Bakaev; A. A. Kulikova (LLC "Endo Press", 2020)
Aim. Determine the nature of the changes of the crystal lattice of nickel-titanium instruments Protaper Universal in the process of repeated autoclaving based on the results to conclude about the influence of multiple sterilization on the characteristics of clinical use of protaper. Materials and methods. is endodontic nickel-titanium instruments of Protaper Universal 21 copies. The instruments were divided into 3 groups of 7 samples, x-ray elemental examination and x-ray diffraction analysis were performed after 1, 4 and 7 cycles of autoclaving at 1340c, pressure 2 bar (1.9 ATM.), time 26 minutes. Results. According to x-ray diffraction, the samples are an alloy of the Ni-Ti system and a material containing iron (presumably steel). In addition to nickel and titanium, iron, chromium, cobalt and zinc were found. With increasing number of repeated autoclaving cycles, the mass fraction of Fe, Co, Zn, Cr is decreased, followed by the disappearance of Fe, Co and Zn. Probably the addition of steel affects the cutting ability of the protapers. Consequently, with a decrease of steel content, the cutting efficiency of nickel-titanium protapers also decreases, which negatively affects their cleaning ability. According to the results of the second study, it was found that with increasing autoclaving cycles, the percentage of Fe is decreased, there were changes in the three obtained diffractograms, which indicated an increase in the number of martensitic phase and a decrease in austenitic. Conclusions. The accumulation of such a fragile and unstable structure as martensite can lead to a decrease in the strength of the material to torsion force and lead to breakage of the instrument during the use. The cutting efficiency of the protapers is also reduced during repeated sterilization cycles, which can be caused by the austenitic and martensitic phase displacement affecting the mechanical properties.